Nodal force distribution of moments on arbitrarily shaped geometries without multi-point constraints - Jäger, Michael; Wartzack, Sandro (Engineering With Computers, 2025)
This paper presents a new approach for converting external moments into nodal forces for the Solid Finite Element Analysis. The proposed approach accurately distributes loads on arbitrarily shaped geometries by utilising the vertices of the Finite Element mesh as a point cloud. This eliminates the need for additional elements and Multi-Point Constraints, overcoming the challenges, complexity and computational cost introduced by these constraints. The proposed approach offers a precise and lightweight solution that enhances the performance of design optimisation scenarios with multi-axial moments on complex, non-convex surfaces. The paper presents comprehensive results that validate the effectiveness and accuracy of the proposed approach, particularly in engineering design optimisation scenarios that require a large number of simulations, such as the topology optimisation of truss nodes. Overall, this method offers a practical and efficient approach for handling moments in Solid Finite Element Analysis. In the presented example, computational cost and complexity were reduced by approximately 14 % compared to commonly used methods for solving Multi-Point Constraint
Keywords: Solid finite element analysis; Nodal forces; Multi-point constraints; Moment load; Point cloud; Optimisation